Everybody likes the piano a direct modern approach to piano fundamental - ESTELLA, Joseph M. (Edward Schubert & Co., 1952)
Skipping fingersnThe whole notenEasy MarchnHold the left hand sownnZig zagnMerrily we roll alongnJumping jacknDaytimenSnow flakes